The work of the Brothers of Mercy detachment in the Russian-Tatar village Koshki of the Samara province during the famine of 1898 - Grigoriy G. Tsidenkov (Историческая этнология, 2025)
In 1898, large areas of the Russian Empire were engulfed by famine caused by the crop failure of 1897. The main areas of the disaster, which lasted for two years, were Novorossiya and the Volga provinces. These regions differed greatly in both their economic situation and the characteristics of the disaster itself. In addition, during the period of instability and upheaval, the mentality of the local peoples became very distinct. These differences had a significant impact on the work of public charitable organizations helping those who were starving. The employees of such organizations were the first in Russia to begin collecting information about the national characteristics of the behavior of the starving population. In the spring of 1899, a detachment of six Brothers of Mercy, led by military doctor A.G. Nedler, arrived in the Koshki village in the Samara district of the Samara province. The Brothers of Mercy Institution was founded by Princess Maria Avgustovna Lobanova-Rostovskaya in St. Petersburg in 1897. This organization offered free two-month courses to train "assistants to the sisters of mercy". The Brothers of Mercy received their "baptism of fire" while working in the famine-stricken districts of the Kherson province in 1898. Their work in this region was considered successful, which is why the Brothers of Mercy were sent to a more difficult area in the Samara province. In the Koshki village the staff encountered a number of unforeseen problems caused by the national and religious characteristics of the mixed Russian-Tatar population of the village. Nevertheless, thanks to the endurance of the staff and the wise management of Lobanova-Rostova, the mission quickly adapted to local conditions and was able to carry out successful work.